ANALISIS PENGELOLAAN MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS PADA PT. SUTRA BENTA PERKASA PEKANBARU - Indah Salsabila Syah; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Working capital management in company is one of the most important thing to improving the profitability. More effective the working capital management will make the profitability increase everytime. This study aims to determine and analyze the application of working capital management in improving profitability at PT. Sutra Benta Perkasa Pekanbaru. In this study using quantitative descriptive data types. The data collection technique used is the technique of interview and documentation on the financial data of PT. Sutra Benta Perkasa Pekanbaru.The analysis results show that the management working capital fluctuaced on the management of cash, management of receivable and management of inventory company still not effective yet for managing the working capital. And management profitability for Return On Investment (ROI) and Return On Equity (ROE) fluctuaced makes company still not effective yet for managing profit through sales. Keywords : Working Capital, Profitability